RAPID DEVELOPMENT OF PHOTOVOLTAIC IN DAYS OF THE GLOBAL ECONOMIC CRISIS - Taurbayev, T. I.; Svanbaev, E. A.; Mussabek, G. K.; Baiganatova, Sh. B.; Dikhanbaev, K. K.; Nikulin, V. E.; Topanov, B. G.; Taurbayev, Ye. T. (Recent Contributions to Physics, 2009)
The world economic crisis of 2007-2009 has concerned many branches of manufacture. But the branches connected with photovoltaic instead of recession demonstrated an unknown increase on about 85 % these years. It is related with that the investments which are not finding the appendices in falling off industries, "flow" in the perspective directions connected with the high technology directions of renewed power.